A regional Report Card on physical activity in children and adolescents: The case of Extremadura (Spain) in the Global Matrix 4.0 - María Mendoza-Muñoz; Antonio Castillo-Paredes; Laura Muñoz-Bermejo; Jorge Pérez-Gómez; José C. Adsuar; Javier Brazo-Sayavera; Raquel Pastor-Cisneros (Elsevier, 2024)
Background/objective: This study presents the first Report Card from Extremadura (Spain), concerning the 4th edition of Global Matrix (GM), which aimed to provide an assessment of Physical Activity (PA) in children and adolescents based on 10 common indicators defined by GM. Methods: This Report Card was developed by 34 experts from 8 public institutions and 5 research groups from Extremadura and audited by the Active Healthy Kids Global Alliance (AHKGA). All documents, up to July 2021, were analyzed to grade the 10 indicators according to the benchmarks set out by the AHKGA (scale ranging from A to F). Results: Information was reported in 8 of the 10 indicators, only Active Play and Active Transportation were not reported due to a lack of local information. The other 8 indicators were graded as follows: Overall Physical Activity: F; Organized Sport and Physical Activity: D+, Sedentary Behavior: D, Physical Fitness: C+, Family and Peers: A, School: C+, Community and Environment: B, and Government: C-. In addition, some of the indicators were evaluated according to gender; boys scored higher than girls in Overall Physical Activity (D-vs. F); Organized Sport and Physical Activity (C vs. D) and Physical Fitness (C- vs. D+). Conclusion: The first Report Card from Extremadura in the GM initiative revealed low compliance with international guidelines on PA and sedentary behavior. Despite high grades for sources of influence, the implemented actions have not been effective yet, and there is no information on Active Play and Active Transportation. These results will allow regional authorities to act at a more local level, as Extremadura's administrative framework allows public administrations and political institutions to act in terms of legislative and budgetary powers among others, which is important for resource allocation.